An improved cuckoo search algorithm for integer programming problems. (2018) - Abdel-Baset, Mohamed; Zhou, Yongquan; Ismail, Mahmoud
This paper presents a novel cuckoo search algorithm called elite opposition - cuckoo search algorithm (ECS) for solving integer programming problems. The opposite solution of the elite individual in the population is generated by an opposition-based strategy in the proposed algorithm and form an opposite search space by constructing the opposite population that locates inside the dynamic search boundaries, then, the search space of the algorithm is guided to approximate the space in which the global optimum is included by simultaneously evaluating the current population and the opposite one. The results show that ECS algorithm has faster convergence speed, higher computational precision and is more effective for solving integer programming problems.